Character evolution of modern eupolypods supports the assignment of the fossil fern Cretacifilix fungiformis to Dryopteridaceae - Regalado, Ledis; Schneider, Harald; Müller, Patrick; Schmidt, Alexander R. (Frontiers in Ecology and Evolution, 2023)
The fossil fern species Cretacifilix fungiformis from mid-Cretaceous Kachin amber from Myanmar was previously assigned to eupolypod ferns by having sporangia with a vertical annulus and sporangial stalks 2-3cells thick, along with monolete spores with a distinct perine. However, due to the insufficient documentation of character states and the unavailability of the holotype, the proposed affiliation of this fossil to derived families of eupolypods requires further study. The recent discovery of additional leaf fragments of Cretacifilix fungiformis from the same amber deposit enabled us to re-evaluate the relationships of this fossil taxon. Newly documented morphological evidence corroborates its placement within the eupolypod ferns. This was achieved by evaluating identifiable features present in the fossil species through an ancestral character state reconstruction utilizing a comprehensive, time-calibrated phylogeny of eupolypod ferns. Our character state reconstruction of extant eupolypod families and genera recovered morphological similarity of Cretacifilix to the closely related genera Arachniodes and Dryopteris, supporting an assignment of this fossil genus to the species-rich family Dryopteridaceae within the Polypodiineae.